2006
DOI: 10.1016/j.jfludis.2006.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Nonword repetition skills in young children who do and do not stutter

Abstract: The purpose of this study was to assess the nonword repetition skills of 24 children who do (CWS; n = 12) and do not stutter (CWNS; n = 12) between the ages of 3;0 and 5;2. Findings revealed that CWS produced significantly fewer correct two-and three-syllable nonword repetitions and made significantly more phoneme errors on three-syllable nonwords relative to CWNS. In addition, there was a significant relationship between performance on a test of expressive phonology and nonword repetition for CWS, but not CWN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
97
5
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 53 publications
8
97
5
2
Order By: Relevance
“…Thus far, findings from several recent studies (Anderson et al, 2006;Byrd et al, 2007;Hakim & Ratner, 2004) support the notion that CWS may have difficulties with phonological encoding. However, in addition to the equivocal findings of Melnick et al (2003), there is another study by Arnold, Conture, and Ohde (2005), whose findings do not support the above contention.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…Thus far, findings from several recent studies (Anderson et al, 2006;Byrd et al, 2007;Hakim & Ratner, 2004) support the notion that CWS may have difficulties with phonological encoding. However, in addition to the equivocal findings of Melnick et al (2003), there is another study by Arnold, Conture, and Ohde (2005), whose findings do not support the above contention.…”
mentioning
confidence: 62%
“…Findings from several recent studies (Anderson et al, 2006;Hakim & Ratner, 2004) provide a preliminary basis for speculation regarding the possible nature of this "mediating factor." These studies revealed that CWS are less successful in their ability to correctly repeat two-and three-syllable nonwords than their normally fluent peers, suggesting that CWS may have difficulty retaining phonological information in working memory.…”
Section: Relationship Between Speech Reaction Time and Vocabulary Meamentioning
confidence: 96%
See 1 more Smart Citation
“…Results indicated that CWS had signifi cant weakness in terms of number of phoneme errors at trisyllabic nonwords but not on the others. In a similar study, Anderson et al [23] investigated nonword repetition skills in younger CWS and CWNS (3.0 and 5.2 years old). These fi ndings revealed that CWS produced signifi cantly fewer correct nonwords and made signifi cantly more phoneme errors on nonword repetitions relative to CWNS.…”
mentioning
confidence: 99%
“…Generally, it has been hypothesized that nonword repetition has emerged as a more sensitive measure of children's linguistic abilities, especially phonological skills. [20][21][22][23] Hence the purpose of this study was to investigate phonological skills in young CWS and also to examine the CRH by measuring a) reaction times (RTs) and b) phonological errors (PEs) through a nonword repetition task involving bisyllabic and trisyllabic nonwords.…”
mentioning
confidence: 99%